A Model of Chronic Disease Management: Israeli Physicians' Approach to Cardiovascular Risk Factor Management. Issue 2 (2nd June 2019) - Bord, Shiran; Zelber‐Sagi, Shira; O'Brien Cherry, Colleen; Yeshua, Hanny; Matalon, Andre; Schuster, Richard J.
Abstract : The prevalence of cardiovascular disease (CVD) death in Israel, a high‐income country that provides universal healthcare, is ~25 percent lower than in the United States. Is better disease management a factor? Primary care physicians answered a web‐based survey asking how they manage patients with CVD risk factors and about the health‐care system at the macro level. Most physicians (53.6 percent) spent 5–10  minutes managing CVD risks; 39.3 percent spent 10–20  minutes. Over 40 percent of physicians scheduled return visits in  less than  3 months. Their emphasis was on either balanced lifestyle and medication management or lifestyle (91 percent), while only 9 percent emphasized medication management. They believe that universal coverage and the motivation of both the doctor and patient are key in the successful outcomes. Israeli physicians provide resource‐intensive disease management, committing time, providing frequently repeated visits, and focusing on a balance of lifestyle and medication management. These practices may provide good chronic disease management and could contribute to reduced cardiovascular death.